PHYTOCHEMICAL CONSTITUENTS AND PROXIMATE COMPOSITION OF BAMBARA GROUNDNUT (Vigna Subterranean) AND PIGEON PEA (Cajanus cajan) UNDERUTILIZED IN CALABAR, CROSS RIVER STATE - Ekpo, Grace Ime; Eteng, Ofem Effiom; Bassey, Stella Oyom; Peculiar, Wlkinson; Eteng, Mbeh (FUDMA Journal of Sciences, 2023)
The proximate constituents and phytochemical compositions of Bambara groundnut (Vigna subterranean) and Pigeon pea (Cajanus cajan) underutilized in Calabar, Cross River States was investigated. The research will provide solutions to food availability and affordability to interlock their abundance in complex carbohydrates, plant-based proteins, unsaturated fatty acids and essential minerals. Bambara groundnut (Vigna subterranean) and pigeon pea (Cajanus cajan) obtained from markets in Anambra State and Ugep, Cross River State. The plant extracts were assessed for the existence of phytochemicals by using standard procedures. Phytochemical screening revealed that the plant species used in this research contained alkaloids, flavonoids, and polyphenols. Proximate analysis of the seeds revealed the moisture content of 9.70% for Bambara groundnut and 10.01% for Cajanus, crude fat of 7.50% for Bambara groundnut and 4.50% for Cajanus cajan, ash content of 3.21% for Bambara groundnut and 3.31% for Cajanus cajan, crude protein of 25.01% for Bambara groundnut and 23.06% for Cajanus cajan, and carbohydrates composition of 70.41% for Bambara groundnut and 71.04% for Cajanus cajan. The presence of phytochemicals such as flavonoids, alkaloids, and polyphenols explained the medicinal action of the plants encountered in their therapeutic usage to meet both domestic and commercial needs.
Keywords: Bambara groundnut; Cajanus cajan; Vigna subterranean; Phytochemical; Polyphenol; Flavonoids